If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6x + -7 = 3x + 10 Reorder the terms: -7 + 6x = 3x + 10 Reorder the terms: -7 + 6x = 10 + 3x Solving -7 + 6x = 10 + 3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3x' to each side of the equation. -7 + 6x + -3x = 10 + 3x + -3x Combine like terms: 6x + -3x = 3x -7 + 3x = 10 + 3x + -3x Combine like terms: 3x + -3x = 0 -7 + 3x = 10 + 0 -7 + 3x = 10 Add '7' to each side of the equation. -7 + 7 + 3x = 10 + 7 Combine like terms: -7 + 7 = 0 0 + 3x = 10 + 7 3x = 10 + 7 Combine like terms: 10 + 7 = 17 3x = 17 Divide each side by '3'. x = 5.666666667 Simplifying x = 5.666666667
| 0.01*x^3-1.8*x^2+165*x=120*x | | (11x+6)+(19x+11)=0 | | x^2+sin(x)=1000 | | 8w-14=9w | | 2.5(6n-3)=4n+1 | | .5(10x-4)-(x+8)= | | 2(q+4)+3= | | 330=x-x(.0475) | | -10a+8-8a=-100 | | 27-5n=-3(2n-1)-2n | | 7x=2.5x+8.8 | | (2x-3y+4)dx+3(x-1)dy=0 | | 4a-20=8a | | 6a+9/12= | | 6(x+7)-20=4x+12 | | 6=x/4-4 | | -7w+5+5w=-11 | | 20x^8-15x^4-x^3= | | 10x-5=-10 | | 7d+10=8d | | 6x+6x=16+4x | | 6-2(d+4)=6 | | x^2-2x-420=0 | | k/12=4 | | (-x-5)(-x+3)=0 | | (-5+-1x)(3+-1x)=0 | | 9a=144a | | 2x^2+1.5x+1=5+1.5x | | 3(4x-2)=12(x) | | y=6-45+0 | | 34x=5+23x | | 12x-y=12 |